Challenges of Burn Mass Casualty Incidents in the Prehospital Setting: Lessons From the Formosa Fun Coast Park Color Party. (2nd January 2019) - Lin, Chien-Hao; Lin, Chih-Hao; Tai, Chih-Yi; Lin, Yu-You; Shih, Frank Fuh-Yuan
Abstract: Objective: A burn mass casualty incident (BMCI) involving 499 patients occurred at a "color party" in Taiwan in June 27, 2015. We implemented a study to identify critical challenges regarding the prehospital emergency care in BMCIs.Methods: A 3-stage, mixed methods study was conducted in 2016. First, a statistical analysis of prehospital management using the data retrieved from the Emergency Medical Management System of the Ministry of Health and Welfare, Taiwan was performed. This was followed by a face-to-face, open-ended interview with the emergency medical technicians and the staff of the emergency operations center who responded to the incident; and the transcription of the interview data into constructed themes.Results: Our study indicated that the signs of inhalation injury needed to be incorporated in the field triage protocol for BMCIs; the collaborative utilization of regional emergency medical services may improve the surge capacity in the field; and an "island-hopping" strategy for patient transportation may allow the healthcare systems to manage the surge of burn patients more efficiently.Conclusions: Current field triage protocols may be insufficient for burn patients and should be further investigated. The practices in field triage, transport capacity, and transfer strategy can be considered as a part of an efficient prehospital emergency response to BMCIs.